Partners in our care: patient safety from a patient perspective. Issue 6 (25th September 2012) - Hovey, R B; Morck, A; Nettleton, S; Robin, S; Bullis, D; Findlay, A; Massfeller, H
Abstract : The voice and role of "patient" in patient safety were explored by the Calgary Health Region's Patient and Family Safety Council perspective and the Calgary Health Region, Calgary, Alberta, Canada—an important collaboration for enhanced patient safety. Insights into patient safety were shared and coauthored in this article by the Patient and Family Safety Council with members of the Calgary Health Region staff. The Patient and Family Safety Council members were asked to respond to articles written about the role of patient in patient safety, without direct communication with patients. The authors of this article intended to demonstrate only a few of the ways in which patient involvement and feedback through partnership turn knowledge into action and help inform patients about safety practices and procedures.